TIMPANOPLASTIAS 11/ III - REVISÃO DE S ANOS (1999- 2003) - Amorim, A. Margarida; Costa, S.; Romão, J.; Tomé, P.; Gonçalves, P.; Neves, J. C.; Paiva, S.; Gapo, C.; Soares, V.; Ribeiro, J.; Gouveia, Lima; Sofia, J. C.; et al. (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.